Calpain-mediated down-regulation of myelin-associated glycoprotein in lysophosphatidic acid-induced neuropathic pain - Xie, Weijiao (2010)
Lysophosphatidic acid receptor (LPA(1)) signaling initiates neuropathic pain through demyelination of the dorsal root (DR). Although LPA is found to cause down-regulation of myelin proteins underlying demyelination, the detailed mechanism remains to be determined. In the present study, we found that a single intrathecal (i.t.) injection of LPA evoked a dose- and time-dependent down-regulation of myelin-associated glycoprotein (MAG) in the DR through LPA(1) receptor. A similar event was also observed in ex vivo DR cultures. Interestingly, LPA-induced down-regulation of MAG was significantly inhibited by calpain inhibitors (calpain inhibitor X, E-64 and E-64d) and LPA markedly induced calpain activation in the DR. The pre-treatment with calpain inhibitors attenuated LPA-induced neuropathic pain behaviors such as hyperalgesia and allodynia. Moreover, we found that sciatic nerve injury activates calpain activity in the DR in a LPA(1) receptor-dependent manner. The E-64d treatments significantly blocked nerve injury-induced MAG down-regulation and neuropathic pain. However, there was no significant calpain activation in the DR by complete Freund’s adjuvant treatment, and E-64d failed to show anti-hyperalgesic effects in this inflammation model. The present study provides strong evidence that LPA-induced calpain activation plays a crucial role in the manifestation of neuropathic pain through MAG down-regulation in the DR.